The Effect of Low Impact Development Implementing on Flood Discharge of Outflow Drainage in the Lakarsantri District Surabaya City - Habibur Rohman; Umboro Lasminto; Yang Ratri Savitri (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2024)
The drainage system in Lakarsantri District, Surabaya, applies a conventional drainage system which only focuses on water quantity. This is shown by flood events that occur in the area and downstream of the channel. A new paradigm in the management of drainage systems is a low impact development concept that focuses on conservation efforts and the use of natural features to carry out small-scale engineering to control surface runoff of rainwater in watersheds. This research aims to find a good model that can be applied with significant influence. This research was carried out by modeling using the SWMM application with 3 scenarios, scenario 1 Porous Pavement LID, scenario 2 Vegetative Swale LID, scenario 3 50% Porous Pavement + 50% Vegetative Swale LID. The results of the modeling show that scenario 1 has the effect of reducing surface runoff discharge by 0,385 ha-m, which in existing conditions has a surface runoff of 6,574 ha-m and then reducing to 6,189 ha-m with an installation percentage of 2,81% of the total area by ​​the research location.